Peningkatan Kemampuan Mengenal Bangun Ruang Melalui Video Animasi Untuk Siswa Tunagrahita Ringan Di SLB C YPPLB Makassar - Sitti Rahmah; Dwiyatmi Sulasminah; Usman Usman (-, 2024)
The problem of this research is that students with mild mental retardation at SLB C YPPLB Makassar have not been able to recognize spatial shapes. The formulation of the research problem is "How to increase the ability to recognize spatial shapes for students with mild mental retardation at SLB C YPPLB Makassar through the application of animated videos?". The purpose of this study was to find out: 1) The ability to recognize spatial shapes for students with mild mental retardation at SLB C YPPLB Makassar before implementing video animation. 2) The ability to recognize spatial shapes for students with mild mental retardation at SLB C YPPLB Makassar after implementing an animated video. 3) Improving the ability to recognize spatial shapes through the application of video animation for students with mild mental retardation at SLB C YPPLB Makassar through the application of video animation. The results showed that the ability to recognize spatial shapes for students with mild mental retardation at SLB C YPPLB Makassar has increased during the use of animated videos in the learning process. Before the application of animated videos, students' abilities were included in the incapable category and after the application of animated videos during learning, students' abilities increased to very capable categories